Addison's disease masking a potentially life-threatening condition. Issue 1 (4th April 2014) - Rojas-Marte, Geurys; Chadha, Sameer; Konka, Sarita; John, Jinu; Malik, Bilal; Hollander, Gerald; Shani, Jacob
Abstract: Addison's disease (AD) is a metabolic disorder that affects the metabolism of potassium. The hyperkalemia that results from this condition can be reflected in the electrocardiogram, which could confound the diagnosis of other cardiac conditions. Such a challenging situation was encountered when a 73-year-old male with history of AD presented to the emergency department with chest pain.